Clinical characteristics with long-term follow-up of four Okinawan families with moderate hearing loss caused by an OTOG variant - Ganaha, Akira (Hum Genome Var, 2019)
We describe the clinical features of four Japanese families with moderate sensorineural hearing loss due to the OTOG gene variant. We analyzed 98 hearing loss-related genes in patients with hearing loss originally from the Okinawa Islands using next-generation sequencing. We identified a homozygous variant of the gene encoding otogelin NM_001277269(OTOG): c.330C>G, p.Tyr110* in four families. All patients had moderate hearing loss with a slightly downsloping audiogram, including low frequency hearing loss without equilibrium dysfunction. Progressive hearing loss was not observed over the long-term in any patient. Among the three patients who underwent newborn hearing screening, two patients passed the test. OTOG-associated hearing loss was considered to progress early after birth, leading to moderate hearing loss and the later stable phase of hearing loss. Therefore, there are patients whose hearing loss cannot be detected by NHS, making genetic diagnosis of OTOG variants highly useful for complementing NHS in the clinical setting. Based on the allele frequency results, hearing loss caused by the p.Tyr110* variant in OTOG might be more common than we identified. The p.Tyr110* variant was reported in South Korea, suggesting that this variant is a common cause of moderate hearing loss in Japanese and Korean populations.